PENERAPAN METODE DISKUSI UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PADA MATERI MENGGUNAKAN PECAHAN DALAM PEMECAHAN MASALAH SISWA KELAS V SDN 003 TEMBILAHAN KOTA KECAMATAN TEMBILAHAN - Saadah, Saadah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2017)
The low mathematics learning outcomes of grade V students is the background of this study, of 18 only 8 (44.45%) are complete, the average value obtained is 55.83. This study aims to improve the results of mathematics learning by applying the method of discussion. This study is a classroom action research conducted in class V SDN 003 Tembilahan Kota, the subject in this study amounted to 18 students consisting of 15 male students and 3 female students. The study was conducted in two cycles, each consisting of two meetings and one daily test. The results of this study states that after applied the method of discussion of mathematics learning outcomes of students of grade V SDN 003 Tembilahan Kota has increased. This is evidenced by: in prasiklus a thorough student is 8 students with an average score of 55.83, in the cycle I complete student is 16 students with an average value of 80.00. And on the second cycle of completed students is 18 students with an average grade of 88.06.